Teachers' Understanding of the Use of Artificial Intelligence to Increase Elementary School Students' Literacy in Enrekang Regency - Ismaya Ismaya; Andi Ahmad Chabir Galib; Syawal Sitonda; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2023)
This research aims to investigate teachers' understanding of the use of artificial intelligence (AI) in an effort to increase the literacy of elementary school (SD) students in Enrekang Regency. Literacy is an important aspect of education that influences students' ability to read, write and understand information. The use of AI in educational contexts has become a topic that is receiving increasing attention, but teachers' understanding of the use of this technology to improve student literacy still needs further research. The research method used is qualitative with a phenomenological approach. Data was collected through in-depth interviews with elementary school teachers in Enrekang Regency. Data analysis was carried out thematically to identify patterns and main findings. Research findings show that the majority of teachers have a basic understanding of artificial intelligence and its potential to improve student literacy. However, there are also some teachers who still feel unsure or have uncertainty regarding the use of AI in an educational context. Factors such as technical readiness, institutional support, and teachers' perceptions of AI effectiveness influence teachers' level of understanding and acceptance of this technology. The results of this research can be the basis for developing training and learning programs oriented towards the use of AI to increase student literacy at Enrekang Regency Elementary School. Efforts to improve teachers' understanding and skills in integrating AI technology in learning can have a positive impact in improving the quality of education at the elementary level.